Mainstreaming of Slums and Informal Sector towards Achieving Inclusive Growth of Durgapur - Harendra Bohra, Rajesh Sharma (Mathematical Statistician and Engineering Applications, 2020)
Pandit Jawaharlal Nehru on the eve of independence made a pledge “for ending of poverty, ignorance, disease and inequality of opportunity.” In India while there is sustained high economic growth, but we are still lagging far behind to fulfill the pledge. There are enough evidences to suggest that there are inequality and lack of inclusiveness in development. Economic growth that is achieving an increase in GDP is seen as a means to uphold the life standard of people, productive employment, and education, health care and so on. Unfortunately the major drawback in this economy is that the growth is not inclusive. The lack of inclusiveness is implied by data on several dimensions of performance in comparison with the economic achievements at national level; even urban morphology of Durgapur bears the testimony of it.